Studies on Chromium-free Conversion coatings on Aluminum - M Oki (Journal of Applied Sciences and Environmental Management, 2010)
The development of a chromium-free conversion coating on aluminum has been studied using transmission electron microscopy (TEM), Auger Electron (AES) and Secondary ion mass spectroscopy (SIMS) techniques. Within the limits of the resolution of the TEM, the coating is uniformly clear and featureless. It is composed essentially of Zirconium Oxide over a diffused layer of Zirconium and Aluminum Oxides